Nutritional Status Overview of Toddler Development in the Coastal Region of Bengkulu City, Indonesia - Amalia, Annisa; Dewiani, Kurnia; Novianti; Yusanti, Linda; Purnama, Yetti; Yulyani, Linda (Journal of Health Sciences and Medical Development, 2024)
The problem of delays in toddler development can be caused by nutritional status. Good nutritional status can affect a person's development. A person's nutritional status depends on nutritional intake and individual needs, if nutritional intake and needs are balanced then the nutritional status will be good otherwise poor nutritional status in toddlers can cause developmental delaysThe purpose of this study was to determine the characteristics of toddlers, characteristics of mothers who have toddlers, frequency distribution of nutritional status and development of toddlers in the coastal area of Bengkulu City. This research method is descriptive-analytic, sampling technique using incidental sampling technique, the analysis used in univariate analysis. The results showed the characteristics of toddlers, namely, the age of the dominant toddler was 36 months old 22.0%, the gender of the dominant toddler was female 52.4%, toddlers had a history of exclusive breastfeeding 75.6%, the last month toddlers suffered from infectious diseases 86.6%. The average age of the mother is 26-35 years old as much as 64.7%. The last education of the mother is the majority senior high school (58.5%), and the majority of the mother's work is housewife (84.1%). Low family income is 58.5%, the number of family members is dominant 4 people 41.5%. Toddlers in the Coastal Region of Bengkulu City have appropriate development with a percentage of 100% accompanied by good nutritional status dominated by toddlers aged 36 months 94.4%, malnutrition dominated by toddlers aged 30 months 11.8%, at risk of overnutrition dominated by toddlers aged 24 months 9.1%. There are no toddlers who experience malnutrition, overnutrition, and obesity. This study concludes that toddlers in the Coastal Region of Bengkulu City have appropriate development and predominantly good nutritional status.